British Association of Dermatologists and U.K. Cutaneous Lymphoma Group guidelines for the management of primary cutaneous lymphomas 2018. (1st March 2019) - Gilson, D.; Whittaker, S.J.; Child, F.J.; Scarisbrick, J.J.; Illidge, T.M.; Parry, E.J.; Mohd Mustapa, M.F.; Exton, L.S.; Kanfer, E.; Rezvani, K.; Dearden, C.E.; Morris, S.L.; et al.
Abstract: Linked Editorial: Wang and Bagot. Br J Dermatol 2019; 180 :443–444 .